Forging Discipline-specific Authorial Voice through Genre : the Role and Place of the Argumentative Essay - BOUKEZZOULA, Mohammed (Journal of Human Sciences, 2016)
The present study investigatesthe teaching /learning of the different aspects of writing in the writing course ,and the evaluation of writing in both the writing course and the content subjects of the curriculum from  both  the faculty staff and the students through the use of two questionnaires designed for this purpose.The great deal of division observed among teachers and confirmed by students about the objectives,approaches ,assessment tools ,the writing resources as well as the focus of feedback in the teaching and evaluation of writing across the curriculum ,is a proof of the prevalence of non-theory based eclecticism which is detrimental to the development of students’academic writing competence.These resultsshow thata three-fold genre-based solution is needed in order to render writing instruction and assessment across this curriculum more conducive to the gradual development of students’discipline-specific writing competence.In this regard,the article proposes an outline of a unit of work for teaching the argumentative essay following the principles of the proposed solution.